Agropolitan Development Strategies in Pujon District, Malang Regency, East Java Province, Indonesia - Diani, Khonita Rahma; Marjono, Marjono; Ciptadi, Gatot (Journal of Indonesian Tourism and Development Studies, 2023)
Agropolitan is one of the regional development concepts used to overcome urbanization caused by development inequality and regional equity. The development of the Pujon District Agropolitan Area is expected to reduce development inequality and poverty levels. This research aims to identify superior commodities, assess sustainability, and develop appropriate strategies for developing the Pujon District into a prosperous Agropolitan area. Quantitative data is used in the research method. Location Quotient (LQ), Multidimensional Scaling (MDS), and SWOT analysis were used to analyze the data. According to the LQ analysis findings, the Pujon District's primary commodities are garlic, potatoes, cauliflower, large chilies, and carrots. Data analysis using MDS on the ecological, economic, socio-cultural, infrastructure, and technology dimensions, as well as the legal and institutional dimensions, reveals that they are "fairly sustainable." According to the findings of the SWOT analysis, the primary key to the strategy for developing agropolitan areas is determining the competitiveness of only commodities so that the higher quality and competitiveness of commodities will encourage the formation of select commodity markets and the formation of dynamic trading activities (marked by high demand from various regions outside the Pujon). Keywords: agropolitan, multidimensional scalling, sustainable agriculture.